(untitled) (Per Musi, 2015)
This paper presents the experience of teaching a Music Sociology course at Federal University of Pará, Brazil, in 2013. The classes focused on the Brazilian genre of capoeira from the point of view of Music Sociology, Music Education, and Ethnomusicology. The main goal of utilizing capoeira as the core of class discussion was to lead a reflection upon non-academic musical cultures present in Brazilian society while focusing on different ways of teaching, learning and performing music.